2006
DOI: 10.1302/0301-620x.88b4.17363
|View full text |Cite
|
Sign up to set email alerts
|

Flexible intramedullary nails for unstable fractures of the tibia in children

Abstract: Flexible intramedullary nailing is gaining popularity as an effective method of treating long-bone fractures in children. We retrospectively reviewed the records and radiographs of 56 unstable fractures of the tibia in 54 children treated between March 1997 and May 2005. All were followed up for at least two months after the removal of the nails. Of the 56 tibial fractures, 13 were open. There were no nonunions. The mean time to clinical and radiological union was ten weeks. Complications included residual ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 21 publications
6
69
0
3
Order By: Relevance
“…Recently, flexible intramedullary nailing has become the preferred method for the treatment of tibial shaft fractures that require operative fixation [6,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, flexible intramedullary nailing has become the preferred method for the treatment of tibial shaft fractures that require operative fixation [6,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The search strategy revealed seven studies, all retrospective case series [6][7][8][9][10][11][12]. Three other studies were excluded due to their small patient numbers: Berger et al [13] reported results from nine patients, Salem et al [14] included five and Huber et al had one [15].…”
Section: Resultsmentioning
confidence: 99%
“…Vallamshetla et al [12] This case series assesses 56 unstable tibial fractures in 54 children treated during an 8-year period from March 1997 to May 2005. This study clearly defines the population with outcome measures of union, time to weight-bearing and function.…”
Section: O'brien Et Al [9]mentioning
confidence: 99%
“…The search for treatment which satisfy most of these criteria has led to an increasing number of surgeons using the elastic intramedullary nails, to treat a variety of pediatric long bone fractures including the tibial shaft. 4,6,10 There are several advantages of this technique. Three-point fixation within the medullary canal allows maintenance of both alignment and rotation for most fractures.…”
Section: Discussionmentioning
confidence: 99%